2007
DOI: 10.1007/s10461-007-9263-2
|View full text |Cite
|
Sign up to set email alerts
|

Micro-credit, Women’s Groups, Control of Own Money: HIV-Related Negotiation Among Partnered Dominican Women

Abstract: A sample of 356 members of women's groups, aged 18-49, in the Dominican Republic were interviewed by trained female interviewers. Data among 273 partnered women were analyzed. The dependent variable, a measure of HIV-related negotiation, was examined for associations with control of own money, level of women's group participation, and ever having received a loan through a micro-credit program. Findings suggest control of own money to be significantly associated with HIV-related negotiation. Ever having receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 21 publications
(20 reference statements)
2
38
1
Order By: Relevance
“…This finding is consistent with the findings of other reports demonstrating the benefit of using a comprehensive health care approach in implementing HIV behavioral prevention interventions [18,19], especially when the disease is stigmatized or when people have limited access to care. Given that African American men have disproportionately less health care insurance [17] and are more likely to receive health care from providers with less training compared to whites [43], a more holistic health promotion approach that includes HIV prevention may be more likely to be effective in reducing HIV sexual risk behavior among these men.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with the findings of other reports demonstrating the benefit of using a comprehensive health care approach in implementing HIV behavioral prevention interventions [18,19], especially when the disease is stigmatized or when people have limited access to care. Given that African American men have disproportionately less health care insurance [17] and are more likely to receive health care from providers with less training compared to whites [43], a more holistic health promotion approach that includes HIV prevention may be more likely to be effective in reducing HIV sexual risk behavior among these men.…”
Section: Discussionsupporting
confidence: 92%
“…The rate of incarceration is also disproportionately high among African Americans. Incarceration reduces opportunities to earn income and thus limits opportunities to break out of the poverty cycle, which in turn affects health care [18,19]. African American men are also more likely than white men to receive delayed diagnoses and treatment for chronic diseases (including HIV infection) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The measures were adapted from those used in previous studies and validated in a Haitian context [10,24,32,33]. The questionnaire was translated into Haitian Creole by Haitian Fonkoze employees and was piloted with five Fonkoze clients to test for validity.…”
Section: Methodsmentioning
confidence: 99%
“…A 2007 study in the Dominican Republic did not show that receiving a microfinance loan through a local women's group was statistically associated with HIV-related negotiation [24]. The two-year IMAGE randomized trial in South Africa originally found no significant change in HIV risk indicators between control and microfinance intervention villages [25].…”
Section: Introductionmentioning
confidence: 97%
“…Individuals recovering from illness, especially female borrowers, may need to divert loans to household expenditures or redirect loans to more profitable businesses within the family. 86,[123][124][125][126][127] We argue that the question is not, "Should PLWHA receive microfinance support?" but rather, "Which PLWHA should receive microfinance support, and what should the support include?…”
Section: Discussionmentioning
confidence: 97%